2020
DOI: 10.2196/preprints.26845
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relationship Between Perceived Risks of Using mHealth Applications and the Intention to Use Them Among Older Adults in the Netherlands: Cross-sectional Study (Preprint)

Abstract: BACKGROUND Considering the increasing demand for health services by older people and the ongoing COVID-19 pandemic, digital health is commonly viewed to offer a pathway to provide safe and affordable health services for older adults, thus enabling self-management of their health while health care systems are struggling. However, several factors cause older people to be particularly reluctant to adopt digital health technologies such as mobile health (mHealth) tools. In addition to previ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that age affects intention (Na et al, 2021;Watanabe et al, 2021;Herzallah et al, 2022); and in this study, age was included as a control variable (Hien et al, 2021;Klaver et al, 2021;Saari et al, 2021). Research on the moderating role of COVID-19 fear in the relationship between satisfaction and travel intention is lacking; therefore, this study proposes the seventh hypothesis: H7.…”
Section: The Moderating Role Of Fear Of Covid-19mentioning
confidence: 87%
“…Previous studies have shown that age affects intention (Na et al, 2021;Watanabe et al, 2021;Herzallah et al, 2022); and in this study, age was included as a control variable (Hien et al, 2021;Klaver et al, 2021;Saari et al, 2021). Research on the moderating role of COVID-19 fear in the relationship between satisfaction and travel intention is lacking; therefore, this study proposes the seventh hypothesis: H7.…”
Section: The Moderating Role Of Fear Of Covid-19mentioning
confidence: 87%